Songs and Chronicles of a Forgotten Neighborhood - Macarro Sender, Marcos (Spain, 2016)
Songs and Chronicles of a Forgotten Neighbourhood is a straightforward and brutal portrait of Palosmás, a marginal neighbourhood in Northern Nicaragua. The hell where lives are enclosed, and their stories are hymns to the courage and human dignity.
Verzio Film Festival Submission
Keywords: Documentary films